1980
DOI: 10.1121/1.384509
|View full text |Cite
|
Sign up to set email alerts
|

Compilation of empirical ultrasonic properties of mammalian tissues. II

Abstract: The compilation of the literature on ultrasonic propagation properties of mammalian tissues [J. Acoust. Soc. Am. 64, 423 (1978)] is continued with the addition of 45 papers yielding over 700 lines of parametric data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(134 citation statements)
references
References 19 publications
4
128
1
1
Order By: Relevance
“…Hence, in translating the nonlinearity propagation seen in water to that seen in tissue for the same beam, for most tissue types it is the change in absorption which is the overwhelming consideration, not the change in B/A (Duck 2010). The absorption coefficients for soft tissue in the literature are for lower signal amplitudes than the ∼1 GPa levels found in this paper, and vary considerably (Burley et al 1980;Goss, Johnston & Dunn 1980;Damianou, Sanghvi & Fry 1997;Bailey et al 2003;Zderic et al 2004;Liu et al 2006;Coussios & Roy 2008). To reduce the range of values available even for the restricted amplitude range of clinical diagnostic device output, it is a standard practice to 'derate' the field values measured in water by 0.3 dB cm −1 MHz −1 , and for the data specific to the tissues and amplitudes occurring in this paper, this is also applied to the predicted values here to estimate the signals that would be detected were the fields to propagate through soft tissue.…”
Section: The Effect Of Tissuecontrasting
confidence: 39%
“…Hence, in translating the nonlinearity propagation seen in water to that seen in tissue for the same beam, for most tissue types it is the change in absorption which is the overwhelming consideration, not the change in B/A (Duck 2010). The absorption coefficients for soft tissue in the literature are for lower signal amplitudes than the ∼1 GPa levels found in this paper, and vary considerably (Burley et al 1980;Goss, Johnston & Dunn 1980;Damianou, Sanghvi & Fry 1997;Bailey et al 2003;Zderic et al 2004;Liu et al 2006;Coussios & Roy 2008). To reduce the range of values available even for the restricted amplitude range of clinical diagnostic device output, it is a standard practice to 'derate' the field values measured in water by 0.3 dB cm −1 MHz −1 , and for the data specific to the tissues and amplitudes occurring in this paper, this is also applied to the predicted values here to estimate the signals that would be detected were the fields to propagate through soft tissue.…”
Section: The Effect Of Tissuecontrasting
confidence: 39%
“…The material constants used for bone were ρ b = 1850 kg/m 3 , λ b = 9306 MPa, μ b = 3127 MPa, η = 40 Pa · s and ξ = 0.1 Pa · s. This produced longitudinal and shear (phase) velocities at 1.5 MHz of 2901 m/s and 1307 m/s and differential specific attenuations of 6.09 dB cm −1 MHz −1 and 49.7 dB cm −1 MHz −1 , respectively. The value of shear attenuation in bone has the most degree of uncertainty as reported in the literature; for example Goss et al (1980) noted experimental values of 7.6 dB cm −1 MHz −1 while a more recent article by White et al (2006) reported (at 0.84 MHz) that shear attenuation was 17 dBMHz −1 , more than four times the value of longitudinal attenuation. Therefore, the higher value of shear attenuation used in this study is felt to be reasonable because of the higher center frequency (1.5 MHz) used.…”
Section: Ultrasound Simulations and Parametersmentioning
confidence: 99%
“…The material in the marrow spaces of the tissue was assumed to be fresh blood. (Goss et al 1968(Goss et al ,1980Selfridge 1985).…”
Section: Ultrasound Simulations and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The software was developed with the use of LabVIEW 7.1 (National Instruments ), implementing these layers (according to tissue properties, as in Table 1 19,20 ), and simulating the passage of a flat wave according to the equations previously described. The software allows the user to define the following parameters of each layer: thickness (x), attenuation coefficient ( ), acoustic impedance (Z), density ( ), specific heat (c), and thermal conductivity (k).…”
Section: The Simulation Softwarementioning
confidence: 99%